2020
DOI: 10.1007/s40869-020-00103-7
|View full text |Cite
|
Sign up to set email alerts
|

For Whom the Games Toll: A Qualitative and Intergenerational Evaluation of What is Serious in Games for Older Adults

Abstract: The aim of this study was to engage older adults in discussions about digital serious games. Using a qualitative exploratory approach, we report observations from more than 100 h of conversations with individuals in the age range 65-90, in a study entitled "Finding better games for older adults" (June 2017-December 2019). Phase 1 (19 older participants, 3 young research students) involved conversations around a quantitative study of cognitive benefits of digital playing (minimum 6 h/person). Phases 2 and 3 inv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
4
1

Relationship

3
7

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 46 publications
1
9
0
Order By: Relevance
“…In other words, the appraisal of media in relation to individual's needs motivated their approach to passive viewing but led to active avoidance and filtering of the negative content out of one's life. This is consistent with a common finding in media studies that choice and self-determination can affect the evaluation of the situation and perceived satisfaction with media [6,14,[33][34][35].…”
Section: Passive Viewing Of Self-curated Information or Entertainment Content Helpssupporting
confidence: 90%
“…In other words, the appraisal of media in relation to individual's needs motivated their approach to passive viewing but led to active avoidance and filtering of the negative content out of one's life. This is consistent with a common finding in media studies that choice and self-determination can affect the evaluation of the situation and perceived satisfaction with media [6,14,[33][34][35].…”
Section: Passive Viewing Of Self-curated Information or Entertainment Content Helpssupporting
confidence: 90%
“…Among the general concerns expressed by older adults are fear of reducing the complexity of human experience with machine learning and artificial intelligence [50], fear of misinformation [51], fear of stigma [52,53], fear of surveillance [54,55], fear of losing control over their lives [56], and general technostress [39,[57][58][59][60]. Of course, these concerns are not specific to older adults, and research suggests that there is a significant pushback against the notion of assumption that older adults are either unwilling or incapable of technology adoption [39,40,61,62].…”
Section: Challenge Of Age As a Recruitment Criterion In Health Techno...mentioning
confidence: 99%
“…The increasing familiarity and age ranges play an important role in this type of classification. In most of the works it is concluded that the creation of a safe, comfortable and accessible space for learning must be considered for serious games, as a valuable tool for learning [35], [41]- [43] Most of the research presented a model-driven engineering that helps serious game developers with tools that reduce development times and abstraction of concepts for serious games. Considering that a video game developer does not know the concepts that a serious game must have incorporated so that the users have an experience with playability.…”
Section: Evaluate Gameplaymentioning
confidence: 99%